Analisa Korelasi Motivasi Koperasi, Manfaat Koperasi dan Kualitas Pelayanan terhadap Partisipasi Anggota - Prisma Jalu Permana, Antonius; Vicka Bayu Wardani, Jovita (Jurnal Informatika Ekonomi Bisnis, 2023)
The existence of cooperatives is expected to be able to realize a populist economy that grows rapidly and is just and in accordance with the goals of sustainable development (SDGs). The participation of members of the Kosayu Credit Cooperative is still considered insufficient. This can be seen from the decrease in the number of members' savings and an increase in Non-Performing Loans (NPL) or members' bad loans. The purpose of this study was to determine the effect of cooperative members' motivation, benefits for members, and cooperative service quality both partially and simultaneously on the participation of Kosayu Kopdit members. The population in this study were all members of the Kosayu Kopdit. From the partial hypothesis testing, it is known that the cooperative motivation variable has a positive effect of 16.4%, the member benefits variable has an effect of 36.2%, and the service quality variable has an effect of 21.7% on the participation of Kosayu Kopdit members. While simultaneously, the variables of motivation to cooperate, the variables of benefits for members, and the variables of service quality jointly affect member participation by 40.4% and the remaining 59.6% is influenced by other factors.